Static and dynamic analysis of rockfill dam using finite-infinite element method - Noorzaei, Jamaloddin; Karami, Morteza; Thanoon, Waleed Abdulmalik; Jaafar, Mohd Saleh (Universiti Putra Malaysia Press, 2005)
In this paper, the dam body and the underneath soil were modeled using coupled finite-infinite elements under plane strain conditions. Initially, static stresses developed in the dam-foundation system due to gravity and hydrostatic loads are evaluated. Elasto-plastic seismic analysis of the dam-foundation system is next carried out by adopting the Drucker-Prager criterion for the material nonlinearity. The equation of motion is solved by New mark incremental time integration technique. The study focuses on the structural behaviour of the dam-foundation system under earthquake excitations. The behaviour in terms of displacement contours, stress distributions and the failure mode are presented.